Antarctic research at a time of crisis: The impact of COVID-19 on the Antarctic research community - Ligget, Daniela; Herbert, Andrea; Badhe, Renuka; Hudson, Katelyn; Kelman, Ilan; Sang Lee, Won; Lorenzo, Cristian A.; Marques Quinteiro, Pedro; Nash, Meredith; Navarro, Diego; Nieboer, Miranda; Pickett, Jennifer; et al.
This presentation will share the results of a survey that aimed at understandingthe impact of COVID-19 on the Antarctic research community. Primarilydesigned to identify the most adversely affected Antarctic researchers andgauge what kind of assistance they might need, the survey, which forms partof an interdisciplinary international research programme on the impact of COVID-19 for the Antarctic community more broadly, also examined the longtermimplications of COVID-19 for National Antarctic Programmes.Over 300 Antarctic research community members, most of them academics,participated in the survey. Preliminary results show that the careers of earlycareerresearchers and those heavily reliant on fieldwork are most adverselyaffected by COVID-19. As expected, relief funds and free access to data,especially for those whose field campaigns were cancelled, would moderatethe impact the pandemic has had on researchers to a certain extent. The survey also reveals that COVID-19 resulted in significant adverse impacts onmental health for Antarctic researchers, with the majority of survey participants noting extreme or moderate dissatisfaction with their mental health and significant increases in anxiety and stress levels, all of which needs to be considered when designing strategies for addressing the impact of COVID-19 in the Antarctic community. Fil: Ligget, Daniela. University of Canterbury; Nueva Zelanda Fil: Herbert, Andrea. University of Canterbury; Nueva Zelanda Fil: Badhe, Renuka. European Polar Board; Países Bajos Fil: Hudson, Katelyn. Bond University; Australia Fil: Kelman, Ilan. University College London; Estados Unidos Fil: Sang Lee, Won. Korea Polar Research Institute; Corea del Sur Fil: Lorenzo, Cristian A. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego; Argentina Fil: Marques Quinteiro, Pedro. Instituto Universitário; Portugal Fil: Nash, Meredith. University of Tasmania; Australia ...